Pemeliharaan Benih Ikan Tambakan (Helostoma temminckii) dengan Padat Tebar Berbeda di Indralaya - Kencana, Citra; Esterlina Sinaga, Chyci; Timoria, Agnes; Dianda, Andra; Wijaya, Ihza; Pasaribu, Seryna Angelica; Yonarta, Danang (Seminar Nasional Lahan Suboptimal, 2023)
Kencana, C., Sinaga, C.E., Timoria, A., Dianda, A., Wijaya, I., Pasaribu, S.A.,& Yonarta, D. (2023). Pemeliharaan Benih Ikan Tambakan (Helostoma temminckii) dengan Padat Tebar Berbeda di Indralaya. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang  21 Oktober 2023. (pp. 223-229). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Kissing gourami (Helostoma temminckii) is a type of freshwater fish whose natural habitat is in tropical climates, specifically Southeast Asia. This research aimed to investigate the effect of stocking density on the growth and survival of Kissing gourami (H. temminckii) in Indralaya. Parameters observed during research included absolute length, absolute weight, feed efficiency, survival and water quality. The results showed that the growth in length, weight, feed efficiency and survival rate of tambakan fish (H. temminckii) in the PA treatment with a stocking density of 40 fish (2 L-1) got the best value, namely with an absolute length of 2.7 cm, weight absolute 1.15 g, feed efficiency 16.83%, and survival 85%. Water quality parameters are within the acceptable range, temperature 25.4-31.3°C, pH 6.77-8.20, dissolved oxygen 2.3-3.3 mg L-1, ammonia 0.018-0.031 mg L-1. Stocking density significantly influences the growth and survival of Kissing gourami. Low density (PA) produces better growth and higher feed efficiency than high density (PB). This research provides insight into optimizing stocking density in pond fish cultivation to increase growth and survival.